CHEMOINFORMATICS AND ITS APPLICATIONS - Wenli XU; Min LING; Jing HU; Ying HUANG; Jia LI; Jianhua YAO (European Scientific Journal, ESJ, 2013)
With development of computer science and network, computer and software are getting more and more applications in scientific research, production and service areas. In silico is an expression used to mean “performed on computer or via computer simulation”. Chemoinformatics is one of in silico technologies employed in researches relating to Chemistry. It is an application of informatics methods to solve chemical problems concerned with molecular design, synthesis design and structural identification. It is an interdisciplinary combining of Computer science, Mathematics and Chemistry. In principle, three methods are included in Chemoinformatics: data-based, logic-based and principle-based. These years, Chemoinformatis has been applied not only in chemical research but also in domains relating to Chemistry, i.e., Drug Discovery, Pesticide Design, Environment Protection, Material Design, Traditional Chinese Medicine (TCM), Food Safety and etc., which relate to Chemistry. Chemoinformatics will be applied in more and more domains relating to Chemistry because “Chemistry is (almost) everywhere and in everything”. Herein, two works: 1. modern mode of chemical research or other works relating to chemical research is proposed, which is combined by thinking, experiment and in silico; 2. in silico platform for pesticide design will be presented.